E-jenayah ancaman alaf digital / Mohamad Zaki Ibrahim - Mohamad Zaki, Ibrahim (2002)
The Internet is the greatest technological innovation since the achievement of the industrial revolution, accomplished through amalgamation of information, communication and digital technology which then created the largest and widest ever computer networking system. Therefore, new sphere known as the Internet which is virtual in nature, also prominently name as cyber-world. Consequently, whole new structures of politicaL economy, social and culturally of society have been forced into us to accept the changes which then inaugurate ·with new electronic practices. Eventually, the Internet was created by the use of inter networking of the computing system throughout the world with help of automated data system. Subsequently, open-up the new frontier of digital ·. development. Unfortunately, this new infrastructure also open-up gap for new breed of criminals to adopt this technologically driven by 'digitizing' the traditional crimes "\vith the ne\V opportunities. With all computing tools and electronic gadgets which they could hold, its seem easier for them to launch attack in the direction of individuaL organizations, groups and even governments in no time. Their capabilities not only be able to commit 'traditional' crimes \vith sophisticated ways, its also pave new electronic crimes which even harder for enforcement to bring them do\vn. This paper will explain types of electronic crime, problems created and methods to control e- criminals.